2016
DOI: 10.2217/bmm-2016-0069
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Monocyte-To-High-Density Lipoprotein Cholesterol Ratio to Predict Bare Metal Stent Restenosis

Abstract: High preprocedural MHR is related to BMS restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…2,3 Inflammation and oxidative stress are involved in atherosclerosis and are thought to contribute to the initiation and progression of ISR. 3,4 Many inflammatory and oxidative biomarkers including C-reactive protein (CRP), monocyte-to-HDL-C cholesterol ratio (MHR), and resting heart rate have been demonstrated to be independent risk factors for atherosclerosis, ISR, and cardiovascular events. [3][4][5][6] In the study by Kundi et al, it was clear that the white blood cell count was higher, whereas neutrophil and lymphocyte count were lower in the ISR (þ) group when compared to the ISR (À) group ( Table 2).…”
mentioning
confidence: 99%
“…2,3 Inflammation and oxidative stress are involved in atherosclerosis and are thought to contribute to the initiation and progression of ISR. 3,4 Many inflammatory and oxidative biomarkers including C-reactive protein (CRP), monocyte-to-HDL-C cholesterol ratio (MHR), and resting heart rate have been demonstrated to be independent risk factors for atherosclerosis, ISR, and cardiovascular events. [3][4][5][6] In the study by Kundi et al, it was clear that the white blood cell count was higher, whereas neutrophil and lymphocyte count were lower in the ISR (þ) group when compared to the ISR (À) group ( Table 2).…”
mentioning
confidence: 99%
“…Likewise, MHR was found to be independently correlated with inhospital major adverse cardiac events and mortality after primary percutaneous coronary intervention (PCI) [45], and with major adverse cardiovascular events in patients undergoing coronary angiography [46] and in patients with acute coronary syndrome (ACS) [47]. Moreover, MHR arose as an independent predictor of in-stent restenosis [48]. As stated above, several lines of reports, which referred the benefit of monocyte countapplied predictive markers for CVD, were augmented.…”
Section: Modified Marker Using Monocyte Count Correlates With Cardiovmentioning
confidence: 99%
“…It was reported that neointimal hyperplasia was triggered by stents, and ISR could result from several mechanisms including inflammation and oxidative stress. [2][3][4] In our recent study, we demonstrated that CHA 2 DS 2 -VASc (congestive heart failure, hypertension, age 75 years, diabetes mellitus, previous stroke/transient ischemic attack, vascular disease, age 65-74 years, female gender) score could be also used as a predictor of ISR. 5 We also found a significant positive correlation between CHA 2 DS 2 -VASc score and C-reactive protein levels.…”
Section: Et Al Reported In Their Recent Article Entitled "Evaluatimentioning
confidence: 99%